Transmission and microevolution of methicillin-resistant Staphylococcus aureus ST88 strain among patients, healthcare workers, and household contacts at a trauma and orthopedic ward - Sun, Long; Zhuang, Hemu; Di, Lingfang; Ling, Xia; Yin, Yiping; Wang, Zhengan; Chen, Mengzhen; Jiang, Shengnan; Chen, Yiyi; Zhu, Feiteng; Wang, Haiping; Ji, Shujuan; et al. (Frontiers in Public Health, 2023)
Background Surgical sites infections (SSIs) caused by Methicillin-resistant Staphylococcus aureus (MRSA) constitute a major clinical problem. Understanding the transmission mode of MRSA is important for its prevention and control. Aim We investigated the transmission mode of a MRSA outbreak in a trauma and orthopedic hospital ward. Methods Clinical data were collected from patients (n = 9) with MRSA infection in a trauma and orthopedic ward from January 1, 2015 to December 31, 2019. The wards (n = 18), patients (n = 48), medical staff (n = 23), and their households (n = 5) were screened for MRSA. The transmission mode of MRSA isolates was investigated using next-generation sequencing and phylogenetic analyses. The resistance genes, plasmids, and single-nucleotide variants of the isolates were analyzed to evaluate microevolution of MRSA isolates causing SSIs. The MRSA colonization-positive doctor was asked to suspend his medical activities to stop MRSA spread. Findings Nine MRSA infected patients were investigated, of which three patients were diagnosed with SSI and had prolonged hospitalization due to the persistent MRSA infection. After screening, MRSA isolates were not detected in environmental samples. The surgeon in charge of the patients with SSI caused by MRSA and his son were positive for MRSA colonization. The MRSA from the son was closely related to the isolates detected in MRSA-induced SSIs patients with 8–9 single-nucleotide variants, while ST88-MRSA isolates with three different spa types were detected in the surgeon's nasal cavity. Comparative genomic analysis showed that ST88-MRSA isolates acquired mutations in genes related to cell wall synthesis, colonization, metabolism, and virulence during their transmission. Suspending the medical activity of this surgeon interrupted the spread of MRSA infection in this ward. Conclusion Community-associated MRSA clones can invade hospitals and cause severe postoperative nosocomial infections. Further MRSA surveillance in the households of health workers may prevent the transition of MRSA from colonization to infection.